LIGHT OLEFIN PRODUCTION USING THE MIXTURE OF HZSM-5/MCM-41 AND -Al2O3 AS CATALYSTS FOR CATALYTIC PYROLYSIS OF WASTE TIRES - FU, RURU; HE, ZHUANGZHANG; QIN, SHIKAI; JIAO, QINGZE; FENG, CAIHONG; LI, HANSHENG; ZHAO, YUN (Chemical Industry & Chemical Engineering Quarterly, 2021)
In this paper, micro-mesoporous HZSM-5/MCM-41 zeolites were prepared by a two-step hydrothermal method using commercial HZSM-5 with two different silica/alumina ratios (38 and 50) as starting materials. The structures, morphologies and acidity of as-prepared zeolites were analyzed using XRD, FT-IR, SEM, N2-adsorption/desorption and NH3-TPD. The HZSM-5/MCM-41 zeolites combined the acidity of microporous HZSM-5 with the pore advantages of mesoporous MCM-41. Mesopores and microspores of 3.34 and 0.95 nm in diameter were found to be present in HZSM-5/MCM-41 zeolites. When they were used to catalyze the pyrolysis of waste tires, the selectivity of light olefins for HZSM-5/MCM-41 prepared using HZSM-5 with the silica/alumina ratio of 50 as starting materials was 21.42%, higher than 18.43% of HZSM-5/MCM-41 synthesized using HZSM-5 with the silica/alumina ratio of 38. In order to further overcome the pore size constraints and mass transfer limitations of HZSM-5/MCM-41 zeolites for catalyzing pyrolysis of waste tires, macroporous γ-Al2O3 were mixed with HZSM-5/MCM-41 and used as catalysts. The selectivity to light olefins for the mixture of γ-Al2O3 and HZSM-5/MCM-41 prepared using HZSM-5 with the silica/alumina ratio of 50 as starting materials was 33.65%, which was obviously enhanced by the introduction of γ-Al2O3.